Classical Antiquity through Ages and Distance - Jijina, Nadia C. (Actual Problems of Theory and History of Art, 2015)
This is an Introduction to the first section of the book that includes papers considering the art of Ancient world. Along with a brief review of the papers, the author puts up a problem of artistic stereotype in the art of Classical antiquity, and its significance for the development of the simultaneous provincial art of the Oikoumene’s outskirts, as well as its influence upon art and figurative culture after Antiquity. While reviewing the publications of the section, the author accentuates the fact that actually all the problems discussed in Classical studies, when touching upon fine arts, appear to disclose figurative schemes elaborated in Classical antiquity. Being applied to artistic practice of various times and regions these programmatic finds of antique artists prove conceptual European artistic unity based upon Hellenic and Roman achievements to exist through ages.
Keywords: Classical antiquity; Classical studies; stereotype in art; figurative schemes; ancient Greeks and barbarians; artistic interpretation